Assessing the Dynamic Linkages between External Debt, Energy Consumption, Inflation, and Oil Prices in Kazakhstan: An Autoregressive Distributed Lag Analysis - Omirtay, Kamshat Altaikyzy; Agabekova, Sholpan Nurtazaevna; Azylkanova, Saule; Yegemberdiyeva, Saule Meyrbekovna; Yessentayeva, Aizhan A.; Aidarova, Aina Bailarovna; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2025)
This study investigates the dynamic linkages between external debt, energy consumption, inflation, and oil prices in Kazakhstan over the period 2001-2024. By applying the Autoregressive Distributed Lag (ARDL) framework, the research uncovers both short- and long-run interactions among these variables. The findings demonstrate that oil prices exert a strong and persistent positive influence on inflation, reflecting Kazakhstan’s structural dependence on global energy markets. In contrast, energy consumption - particularly with a lagged effect - contributes to moderating inflationary pressures, underscoring the role of efficient energy use in stabilizing prices. The results also reveal that external debt, while less significant in the short term, remains a long-run concern due to its potential to weaken resilience if not managed prudently. Diagnostic and stability tests confirm the robustness of the model, highlighting the presence of a stable long-run equilibrium. Policy implications point to the importance of countercyclical fiscal and monetary strategies to cushion oil price shocks, investment in energy efficiency to align growth with sustainability, and prudent debt management to safeguard macroeconomic stability. Overall, the study emphasizes the need for Kazakhstan to diversify its growth model while maintaining stability in the face of global energy transitions and external vulnerabilities.